A moisture differential technique for extraction and maintenance of imported fire ant colonies under laboratory conditions - Farhan Mahmood Shah; Ikhlas A. Khan; Abbas Ali (Scientific Reports)
Abstract Establishing and maintaining colonies of imported fire ants (IFA) (Hymenoptera: Formicidae) in the laboratory are crucial for research. Dehydration is one of the major mortality factors in IFA, and the ants tend to relocate from dry to moist places. In our laboratory, we developed a moisture differential technique to extract fire ant colonies from mound materials. In this technique, the shoveled mound soil was dried by spreading in trays at room temperature. Standard glass test tubes half filled with water and plugged with cotton were placed in drying trays to provide a moist habitat. The gradual loss of moisture created a differential between the moist cotton in test tubes and drying soil in trays. Once the soil dried out, IFA moved from trays to moist cotton in the test tubes to avoid dehydration. All stages including the queens were successfully extracted using this technique. In a comparative study, this method recovered 52% more colony mass of hybrid fire ants than the standard water dripping method. Post separation colony survival was also significantly higher in this method as compared to the water dripping method. In addition to separating and maintaining IFA colonies, the moisture differential technique may have additional applications, especially in conducting behavioral bioassays where workers with active digging behavior are needed. Maintenance of laboratory colonies consisting of all life stages in plastic bottles using this new method mimics the field populations that are required to conduct behavioral bioassays.